Kinematika in dinamika: zbirka nalog - Vesenjak, Matej (University of Maribor Press, 2017)
Kinematics and Dynamics. Book of solved problems and exercises. The book of solved problems and exercises was introduced as didactic support for the subject Kinematics and dynamics at the Faculty of Mechanical Engineering, University of Maribor. The solved problems and exercises are also coherent with the textbook of the above mentioned subject. A basic level of knowledge in the field of statics and mathematics is expected to comprehend the book of solved problems and exercises.